Bridging Housing Preferences and Pricing Strategies in Jakarta: A Critical Review - Bedi, Abdullah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Jakarta’s housing market is shaped by consumer preferences and pricing strategies, with affordability posing a major challenge, especially for young adults. The post-pandemic preference for landed houses and transit-oriented developments highlights the growing demand for accessibility and functionality over status. Developers must integrate sustainable and multicriteria methodologies to align housing supply with evolving urban policies. This study analyzes market trends, consumer behavior, and pricing strategies to identify key housing sector influences. Findings indicate that consumer preferences drive developers' pricing approaches, requiring flexibility to address diverse market segments. While value-based pricing is profitable, implementation challenges necessitate improved customer engagement. Differentiated pricing strategies, including green housing subsidies, can support sustainability and affordability. Location, amenities, and infrastructure significantly impact pricing, underscoring the need for strategic planning. Bridging the gap between market supply and consumer demand is vital for housing policy. Effective strategies should incorporate segmentation insights and dynamic pricing to enhance accessibility. Collaboration among policymakers, urban planners, and developers is essential for inclusive, sustainable urban growth.